Influencia del índice de cosecha sobra la calidad sensorial del grano de cacao (Theobroma cacao L.) del clon ccn-51 en la provincia de mariscal Cáceres – San Martín - Burga Gamonal, Enilda (2016)
This study aimed to determine the influence of optima! harvest index clone cacao CCN-51 on the sensory quality of the grain, by physical, chemical and sensory characterization. Parameters harvest cocoa beans clone CCN-51 corresponded to three stages of maturity. The cobs were pintonas with reddish violet bands, the mature ear, were considered to discoloration from 50 to 75% and the ears were those whose overripe staining was greater than 75% yellow Samples of the beans were harvested three stages of maturity (ripening fruit, ripe and overripe) and fermented in wooden crates for seven days, evaluating physical parameters in the seed coat and cotyledon (soluble solids) and chemical (pH and acidity) every 12 hours of fermentation. The drying of the beans for all treatments was 6 days and the fermentation parameters were evaluated .percentage. For sensory evaluation liquor is obtained from the dried grains and worked with three experimental tria Is. In Study 1, three states of maturity (ripening fruit, ripe and overripe) at day O retention were evaluated. The results show an effect of maturity on the sensory quality of the grain, i.e. overripe beans showed a mean score in relation to acidity (4.24), astringency (4.13), and bitterness (4.53) In Study 11, three states of maturity were assessed with 3 day retention where possible to confirm the results of the above test, the mature and over mature grains promote optima! fermentation. The results of this tria! indicated that the rate of harvest ripe grains favored retaining three days with mean seores of fruit flavor (4.89) and citric (3.59). Finally, in Study 111, the grains were harvested at three stages of maturity with 6 days of retention. lt was observed that the effect of the improved grain retention citrus flavor attribute with a mean score (3.83). Furthermore, the best treatment penton state corresponded to maturity.